THE DEVELOPMENT OF FUZZY EXPERT SYSTEM TO DIAGNOSE INTERNIST DESEASE (CASE STUDY OF DIABETIC DESEASE) - Suzy Puspita Dewi, Ni Putu Suzy Puspita Dewi (Universitas Pendidikan Ganesha, 2012)
The purpose of this research was to design and to implement a system called fuzzy expert system for internist diagnostic, where the system is used to help user for checking percentage of diabetic risk with the optimal and efficient in terms of time. This research was software engineering system, which used the stages of the procedure the System Development Life Cycle (SDLC). The stages of the SDLC procedure used consists of (1) the phases of data collection using the methods of library research, observation and interviews, (2) the requirement analysis phase of software using simple additive weight methods, (3) the stages of design or software design, (4) the stage of development or implementation of software, and (5) the stages of testing. The result of this research were (1) the needs analysis system which consists of two main processes namely, the determination of regional and fuzzy rules for each criteria to be used in diagnostic, and calculation of patient data for finding the percentage of diabetic risk, (2) the design of a system that includes a functional model of software, data structure software which consists of 12 tables, and interface software, and (3) the implementation of the system by using Visual Basic 6.0 programming language and DBMS 7.24 Navicat MySQL is supported by other components such as Wamp Server, and MySQL Connector ODBC 5.1.5 Win32 as a liaison between the program with the database.